Azaruthena(II)‐bicyclo[3.2.0]heptadiene: Key Intermediate for Ruthenaelectro(II/III/I)‐catalyzed Alkyne Annulations. Issue 27 (12th May 2020) - Yang, Long; Steinbock, Ralf; Scheremetjew, Alexej; Kuniyil, Rositha; Finger, Lars H.; Messinis, Antonis M.; Ackermann, Lutz
Abstract: A ruthenium‐catalyzed electrochemical dehydrogenative annulation reaction of imidazoles with alkynes has been established, enabling the preparation of various bridgehead N‐fused [5, 6]‐bicyclic heteroarenes through regioselective electrochemical C−H/N−H annulation without chemical metal oxidants. Novel azaruthenabicyclo[3.2.0]heptadienes were fully characterized and identified as key intermediates. Mechanistic studies are suggestive of an oxidatively induced reductive elimination pathway within a ruthenium(II/III) regime. Abstract : New mechanism : A ruthenium‐catalyzed electrochemical dehydrogenative annulation reaction of imidazoles with alkynes delivers bridgehead N‐fused [5, 6]‐bicyclic heteroarenes through regioselective C−H/N−H annulation without metal oxidants. Novel azaruthenabicyclo[3.2.0]heptadienes were identified as key intermediates. Mechanistic studies suggest an oxidatively induced reductive elimination pathway within a ruthenium(II/III) regime.